BS EN IEC 61462. Composite hollow insulators. Pressurized and unpressurized insulators for use in electrical equipment with rated voltage greater than 1 000 V. Definitions, test methods, acceptance criteria and design recommendations. (1st January 2021) - British Standards Institution,
No abstract available